Biomimetic, antiadhesive surface structure inspired by the calamistra setae of cribellate spiders for electrospun nanofiber handling - Lifka, Sebastian; Stecher, Christoph; Meyer, Marco; Joel, Anna-Christin; Heitz, Johannes; Baumgartner, Werner (Frontiers in Ecology and Evolution, 2023)
Due to their excellent surface-to-volume ratio, nanofibers (i.e., fibers with a diameter of approximately 10 to 800 nm) are of increasing interest to engineers and scientists in a broad spectrum of applications. However, due to van der Waals forces, these nanofibers tend to adhere strongly to any surface, which makes further processing very challenging. In nature, we find animals that can easily handle nanofibers: Cribellate spiders use a comb-like structure, the so-called calamistrum, to produce, handle, and process nanofibers. Due to a fingerprint-like surface nanostructure, nanofibers do not adhere to the calamistrum. The principle interaction between this fingerprint-like surface nanostructure and single nanofibers has recently been described in a publication. The fingerprint-like surface structure was replicated on a technical metal surface using laser-induced periodic surface structures, which resulted in material properties resembling those of the natural model. We went a step further and took a closer look on an additional structural feature of the calamistrum much larger than the fingerprint-like surface structure. A theoretical approach to describing the influence of a fiber preload, which may become a dominant effect if the fiber dimensions are small compared to the surface structure dimensions, on the adhesion of the fiber to these large surface structures was derived. Our theory was verified experimentally for artificial electrospun polyamide 6 nanofibers on surface-structured samples made of titanium alloy. A dramatic reduction in adhesion compared to unstructured, flat surfaces was proven.